2017
DOI: 10.1167/iovs.17-21679
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights Into the Phenotypical Spectrum of KIF11-Associated Retinopathy, Including a New Form of Retinal Ciliopathy

Abstract: Progressive retinal degeneration in KIF11-related retinopathy indicates a role for KIF11 not only in ocular development but also in maintaining retinal morphology and function. The remarkable variability of the ocular phenotype suggests four different types of retinopathy which may overlap. KIF11 should be considered in the screening of patients with retinal dystrophies because other syndromic manifestations may be subtle. Evaluation of head circumference may be considered as a potential shortcut to the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…To date the relationship between IRAK4 and KIF11 has not been investigated mechanistically and evidence for a KIF11 function in cilia is limited. However, a recent study of inherited KIF11-associated retinopathies has provided some support for the idea the protein localizes to cilia, and that these diseases represent a class of ciliopathy (55). These relationships are worth further evaluation in the context of ADPKD; like cancer, a disease in which inflammation plays an important role in disease pathogenesis, among many other signaling commonalities (49,50,56).…”
Section: Discussionmentioning
confidence: 99%
“…To date the relationship between IRAK4 and KIF11 has not been investigated mechanistically and evidence for a KIF11 function in cilia is limited. However, a recent study of inherited KIF11-associated retinopathies has provided some support for the idea the protein localizes to cilia, and that these diseases represent a class of ciliopathy (55). These relationships are worth further evaluation in the context of ADPKD; like cancer, a disease in which inflammation plays an important role in disease pathogenesis, among many other signaling commonalities (49,50,56).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in KIF11 have been shown to cause familial exudative vitreoretinopathy associated with retinal detachment [27]. Birtel et al, revealed that KIF11 is important in both ocular development and the maintenance of retinal morphology and function and defects in this protein have been associated with retinal ciliopathy [28]. KIFs are motor proteins involved in the activities of the centrosome and spindle during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…EG5 also has non-mitotic functions such as involvement in endothelial cell lineage proliferation, secretory protein trans portation, and protein translation [Bar- , 2011;Exertier et al, 2013;Wakana et al, 2013]. EG5 possibly also has a role in the cilia [Birtel et al, 2017]. Jones et al [2014] assessed 37 individuals with KIF11 mutations and found microcephaly, ocular abnormality, lymphedema, epilepsy, and cardiac anomaly as major clinical features.…”
Section: Discussionmentioning
confidence: 99%